Zinc is a critical regulator of placental morphogenesis and maternal hemodynamics during pregnancy in mice. Issue 1 (December 2017) - Wilson, Rebecca; Leemaqz, Shalem; Goh, Zona; McAninch, Dale; Jankovic-Karasoulos, Tanja; Leghi, Gabriela; Phillips, Jessica; Colafella, Katrina; Tran, Cuong; O'Leary, Sean; Buckberry, Sam; Pederson, Stephen; et al.
Abstract Zinc is an essential micronutrient in pregnancy and zinc deficiency impairs fetal growth. We used a mouse model of moderate zinc deficiency to investigate the physiological mechanisms by which zinc is important to placental morphogenesis and the maternal blood pressure changes during pregnancy. A 26% reduction in circulating zinc (P = 0.005) was exhibited in mice fed a moderately zinc-deficient diet. Zinc deficiency in pregnancy resulted in an 8% reduction in both near term fetal and placental weights (both P < 0.0001) indicative of disrupted placental development and function. Detailed morphological analysis confirmed changes to the placental labyrinth microstructure. Continuous monitoring of maternal mean arterial pressure (MAP) revealed a late gestation decrease in the zinc-deficient dams. Differential expression of a number of regulatory genes within maternal kidneys supported observations on MAP changes in gestation. Increased MAP late in gestation is required to maintain perfusion of multiple placentas within rodent pregnancies. Decreased MAP within the zinc-deficient dams implies reduced blood flow and nutrient delivery to the placenta. These findings show that adequate zinc status is required for correct placental morphogenesis and appropriate maternal blood pressure adaptations to pregnancy. We conclude that insufficient maternal zinc intake from before and during pregnancy is likely to impactin utero programming of offspring growth and development largely through effects to the placenta and maternal cardiovascular system.